Determinants of carry trades in Central and Eastern Europe - Andreas Hoffmann (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2011)
In this paper, I analyze determinants of carry trade returns in Central and Eastern Europe (CEE). I show that carry trades to CEE were lucrative due to interest rate spreads between the funding and investment currency from 2004 to 2006. They became unprofitable when liquidity risk and exchange rate volatility increased after 2007. The analysis suggests that the exchange rate regime of the CEE economy matters for carry trade returns. Overall, exchange rate stabilization, particularly via managed floats, seems to allow for the highest profit opportunities.
Keywords: E32; E44; F31; G11; 330; carry trades; emerging markets; exchange rates; Devisenhandel; Zinsparität; Devisenspekulation; Kapitalertrag; Wechselkurssystem; Osteuropa